QUEER CRIMES & CRIMINAL JUSTICE - Bhatt, Mithilesh Narayan ([S.l.] : ROUTLEDGE, 2022)
The Queer/Sexual minority which interalia includes lesbian, gay, bisexual, and transgender (hereinafter LGBT) people is not a new phenomenon in today's scenario. LGBT share a particular experience of their own sexual desires, as potentially directed toward a person of the same gender. They have transformed these experiences, desires, and practices into a social identity, a sexual orientation, which serves as a marker of individual selves and of a group. This study shows that discrimination and abuse from homophobic/transphobic world in which there is full permission to treat LGBT with cruelty makes it difficult for them to maintain a strong sense of well-being and self-esteem. Study reveals that in India LGBT livesare more secretive as they are suppress to come out easily. This book based on study concludes with some strong and viable recommendations, which are requisite to ensure safe and proper place to LGBT peoplein society, inculcating humane approach into laws and the criminal justice system. Education and awareness programmes through various means and various places can bring positive changes. Note: T& F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
OCLC-licensed vendor bibliographic record.
Keywords: LAW / Gender & the Law; Gays -- Legal status, laws, etc; Gays -- Violence against; Sexual minorities -- Legal status, laws, etc; Sexual minorities -- Violence against; Human rights; Criminal justice, Administration of